Re-Bounding Emergency Lawmaking in Indonesia: Constitutional Design, Parliamentary Oversight, Islamic Law Perspectives, and Accountability After COVID-19 - Dian Furqani Tenrilawa; Achmad Ruslan; Aminuddin Ilmar; Marten Arie; Lily Bauw (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2026)
Emergency governance repeatedly tests the constitutional separation of powers among the executive, legislature, and judiciary. Indonesia’s Constitution equips the President with an acceleration instrument—Government Regulations in Lieu of Law (Perppu)—while requiring parliamentary approval as a condition of democratic legitimacy. The COVID-19 pandemic exposed the tension embedded in this design: expert-driven demands for rapid action can widen executive discretion, whereas legislative and judicial oversight often cannot operate at ordinary speed. Using a normative juridical approach that combines constitutional doctrinal analysis, principle-based comparative assessment of emergency governance literature, and maqāṣid al-sharīʿah analysis, this study examines (i) the constitutional and statutory framework governing Perppu and emergency administration, (ii) the ways crisis governance reshapes executive–legislative relations, and (iii) institutional design features capable of reconciling rapid decision-making with democratic accountability. It argues that Indonesia should move from an event-based notion of “emergency” toward a constrained decision-making architecture anchored in sunset clauses, strengthened post-decision parliamentary scrutiny, transparent proportionality reasoning, and expedited constitutional review. The article proposes an Emergency Lawmaking Accountability Framework operationalized through mandatory reporting, oversight triggers, and audit-ready documentation of necessity assessments and rights impacts, aiming to preserve crisis responsiveness while reinforcing checks and balances and reducing incentives for executive aggrandizement in future emergencies. The article further situates the Framework within Islamic legal tradition—specifically the doctrines of darūrah (necessity), maqāṣid al-sharīʿah (objectives of Islamic law), and al-maslahat al-ʿāmmah (public interest)—arguing that Islamic jurisprudence independently supports the normative requirements of bounded emergency governance: necessity must be proportionate and time-limited, power must serve the public welfare (hifz al-nafs, hifz al-māl), and those who exercise authority must do so transparently and accountably (amānah). This contextualized Islamic law dimension both enriches and legitimises the proposed reform framework within Indonesia’s Muslim-majority constitutional democracy